An assessment of the rural consumer food environment in Newfoundland and Labrador, Canada. Issue 4 (4th July 2019) - Mah, Catherine L.; Pomeroy, Stephanie; Knox, Bruce; Rynard, Vicki; Caravan, Melissa; Burgess, Lesley; Harris, Rebecca; Minaker, Leia
ABSTRACT: Rural residents face disparities in economic and geographic access to retail sources for healthy, quality and affordable food, but there remains a relative paucity of rural research on the in-store consumer food environment. We conducted a census of the rural consumer food environment in Canada's easternmost province, Newfoundland and Labrador (NL), where the burden of noncommunicable diseases is disproportionately high and industry data suggest convenience stores are a dominant retail presence. We audited n  = 78 stores (23% supermarkets, 56% convenience stores, and 21% gas stations with convenience), using a nutrition environment measures survey-store adapted for NL comprised of 14 measures encompassing 98 food items. This paper reports on key findings on store characteristics as well as the availability, variety, and quality of food items in key product categories, and the implications for intervention development.